Pengembangan Media Pembelajaran Interaktif Articulate Storyline Materi Zat Aditif Kelas VIII SMP - ., Mutia; Istyadji, Maya; Hafizah, Ellyna (CV. ITTC INDONESIA, 2023)
Lack of teacher innovation in classroom learning which only uses textbooks and worksheets containing only a few pictures and text, so interactive learning media are needed which contain animation, audio and video that attract students to learn and understand the lesson. This research aims to describe the validity and practicality of the interactive learning media Articulate Storyline. This research uses the Research and Development (R&D) method with the ADDIE (Analyse, Design, Develop, Implement and Evaluate) development model. Data collection techniques use media expert and material expert validation sheets as well as student response questionnaires. The research results showed that the interactive learning media Articulate Storyline obtained a media expert validity score of 0.83 while the material expert validity was 0.84. The learning media was tested on thirteen students in small groups and obtained a score of 74.5%. Based on the results, it can be concluded that the interactive learning media Articulate Storyline additive material is stated to be very valid and practical for use in science learning in junior high schools.